High progesterone levels on the day after HCG injection has no effect on clinical pregnancy outcomes in in vitro fertilization-embryo transfer - Liang, Zhuo; Huang, Qiuyan; Huang, Jiwei; Wu, Jinxiang; Zeng, Dingyuan; Huang, Pinxiu (Frontiers in Endocrinology, 2024)
Background: This study investigates the potential impact of high progesterone (P) level on the day following human chorionic gonadotropin (HCG) injection on the clinical pregnancy outcomes of in vitro fertilization-embryo transfer (IVF-ET).Methods: Retrospective analysis was conducted on 6418 cycles of IVF-ET performed at Liuzhou Maternal and Child Health Hospital between August 2020 to December 2021. Excluding cycles with progesterone levels ≥1.5ng/ml on HCG injection, a total of 781 cycles were identified according to the standard, and they were divided into five groups according to the progesterone level on the day after HCG: Group A: progesterone level < 2.5 ng/ml (n = 128); Group B: 2.5 ng/ml ≤ progesterone level < 3.5 ng/ml (n = 174); Group C: 3.5 ng/ml ≤ progesterone level < 4.5 ng/ml (n = 153); Group D: 4.5 ng/ml ≤ progesterone level < 5.5 ng/ml (n = 132); Group E progesterone level ≥5.5 ng/ml(n=194). Comparative analyses of clinical data, including general clinical data, and clinical pregnancy outcomes such as clinical pregnancy rate, miscarriage rate, and live birth rate were performed among these groups.Results: There were significant differences in estradiol levels on HCG injection, but there were no differences in available embryo rate, clinical pregnancy rate, miscarriage rate, and live birth rate. Binary logistic regression analysis showed that there was no significant correlation between P level on the day after HCG injection and the live birth rate.Under the condition of low P level on HCG injection, high progesterone levels on the day after HCG injection does not affect the clinical pregnancy outcomes of IVF-ET.